B1‐Mobilstor: Materials for Sustainable Energy Storage Techniques – Lithium Containing Compounds for Hydrogen and Electrochemical Energy Storage1. Issue 10 (17th June 2014) - Böhme, Bodo; Bonatto Minella, Christian; Thoss, Franziska; Lindemann, Inge; Rosenburg, Martin; Pistidda, Claudio; Møller, Kasper T.; Jensen, Torben R.; Giebeler, Lars; Baitinger, Michael; Gutfleisch, Oliver; Ehrenberg, Helmut; et al.
<x xml:space="preserve">Abstract</x> New material concepts for hydrogen storage and lithium ion batteries are investigated in the joint ECEMP project B1 – Mobilstor. Chemical composition are essential for the performance of a storage material. A certain state of material can be effectively analyzed by in situ methods to obtain a maximum of information. For hydrogen storage the LiNH2MgH2 system and as lithium ion battery anode the Ge(cF136) allotrop are highlighted under this issue. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>